The design profession and ageing in place - Spanbroek, Nancy (2005)
Design Associations and the media have a responsibility to the community to promote good aesthetic and innovative universal housing design solutions. This could be encouraged through awards and publications that focus on excellence in universal design. Housing designers have a responsibility to both the present and future users, and need to be encouraged to integrate universal design features into the design of the home.